Grupa zewnętrzna granfalonu jako przykład skazanego na dyskryminację Innego - Łukowski, Piotr (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Granfalloon is a sociopsychological technique of organizating people in a strongly emotionally identified ingroup. A set of various kinds of emblems is the only way successfully defining granfalloon. In means that no idea, no rational motivation nor rational argument is connected with this social phenomenon. That is why granfallooon is strictly related to the minimal group paradigm. The lack of worth results in the seemingly inexplicable power and unusual vitality of the granfallooon. Unfortunately, it makes granfalloon an extremely dangerous phenomenon, especially for members of granfalloon’s outgroup. Those people are defined as enemies of the granfalloon. The Third Rich is an example of the particularly pathological granfalloon with precisely defined outgroup of Another, a society of Jews condemned to extermination. The Ron Jones’s Third Wave Experience has proved that this technique, also in its really dangerous form, can come into being even in an exclusive school of pupils coming from respectable families living in an old democracy. Undoubtedly, educationalists, teachers and class tutors should possess knowledge about granfalloon as well as the Third Wave Experience.